Visionary Leadership Strategies for Sustaining Madrasah Culture in Industry 4.0 - Syam, Aldo Redho; Supadi, Supadi; Mayasari, Linda Ika; Takdir, Muh.; Noh, Mohd Aderi Che (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – The purpose of this study is to explore visionary leadership strategies for sustaining and developing madrasah culture at the secondary school level (e.g., MTs and MA) in the industry 4.0 era. It examines how effective leadership can preserve traditional values while adapting to technological advancements in education.Method – A literature review approach was employed, analyzing data from databases such as Google Scholar, JSTOR, and Scopus (2010-2025). Keywords included "visionary leadership," "madrasah culture," "Industry 4.0," and "educational leadership." Inclusion criteria focused on peer-reviewed articles, books, and conference proceedings related to madrasah leadership, with exclusion criteria eliminating studies not directly connected to the subject. The quality of studies was assessed using the CASP checklist. Findings – The findings indicate that the effectiveness of madrasah leaders is crucial in preserving and developing madrasah culture in the industry 4.0 era. Visionary leadership is identified as the most effective model, with key strategies such as fostering a long-term, adaptable culture, positioning the leader as an agent of change, aligning goals with technological advancements, and promoting professional development through coaching and collaborative learning (e.g., Professional Learning Communities). The study emphasizes that successful leadership should focus on measurable outcomes, such as increased teacher collaboration, student engagement with technology, and improved educational performance in line with Industry 4.0 standards. Research Implications – Madrasah leaders must adopt visionary leadership to navigate the challenges of Industry 4.0. By implementing these strategies, leaders can ensure the sustainability of madrasah culture while integrating technological advancements. Future research should focus on empirical studies assessing the practical application of these strategies, particularly through longitudinal and case studies across diverse madrasahs.